Does midwife experience affect the rate of severe perineal tears?. Issue 2 (15th February 2017) - Mizrachi, Yossi; Leytes, Sophia; Levy, Michal; Hiaev, Zvia; Ginath, Shimon; Bar, Jacob; Kovo, Michal
Abstract: Background: Our aim was to study whether midwife experience affects the rate of severe perineal tears (3rd and 4th degree). Methods: A retrospective cohort study of all women with term vertex singleton pregnancies, who underwent normal vaginal deliveries, in a single tertiary hospital, between 2011 and 2015, was performed. Exclusion criteria were instrumental deliveries and stillbirth. All midwives used a "hands on" technique for protecting the perineum. The midwife experience at each delivery was calculated as the time interval between her first delivery and current delivery. A comparison was performed between deliveries in which midwife experience was less than 2 years (inexperienced), between 2 and 10 years (moderately experienced), and more than 10 years (highly experienced). A multivariate regression analysis was performed to assess the association between midwife experience and the incidence of severe perineal tears, after controlling for confounders. Results: Overall, 15 146 deliveries were included. Severe perineal tears were diagnosed in 51 (0.33%) deliveries. Women delivered by inexperienced midwives had a higher rate of severe perineal tears compared with women delivered by highly experienced midwives (0.5% vs 0.2%, respectively, P =.024). On multivariate regression analysis, midwife experience was independently associated with a lower rate of severe perineal tears, after controlling for confounding factors. Each additional year of experience was associated with a 4.7% decrease in the risk of severe perineal tears (adjusted OR 0.95 [95% CI 0.91–0.99, P =.03). Conclusion: More experienced midwives had a lower rate of severe perineal tears, and may be preferred for managing deliveries of women at high risk for such tears.